Pemberian Buah Naga (Hylocereus Polyrhizus) Terhadap Penurunan Kadar Glukosa Darah Pasien DM Di Wilayah Kerja Puskesmas Tanjung Karang - Tika Hadi; Ni Ketut Sri Sulendri; Fifi Luthfiyah; Aladhiana Cahyaningrum (Poltekkes Kemenkes Mataram, 2018)
Background. In West Nusa Tenggara the highest prevalence of Diabetes Mellitus is Bima (2.5%). In the city of Mataram the prevalence of diabetes mellitus is around 1.7% and ranks 3rd in 10 districts in West Nusa Tenggara. The 2013 Mataram City Health Profile states that DM is the third highest number of infectious diseases in the city of Mataram. In regulating diet, people with Diabetes Mellitus are advised to pay attention to carbohydrate and fiber intake because it is important in controlling blood glucose. One of the fruits that can be used as blood sugar control is Dragon Fruit (Hylocereus) which has the advantage of being rich in fiber, calcium, magnesium, potassium and sodium. Objective: To determine the effect of giving dragon fruit to the decrease in blood glucose levels when patients with Diabetes Mellitus in Tanjung Karang Health Center.Research Methods. This type of research is Quasi Experiment with a pre-post control group design. The subjects were divided into 2 groups, namely the treatment group that was given 250 grams of red dragon fruit / day and the control group was not given dragon fruit. Giving dragon fruit is done every day for 10 days. GDS level measurements were carried out using the GCU tool. Blood is taken the day before the intervention and one day after the intervention. Statistical analysis using Independent sample t-test, and Paired t-test.Research Result. There was a difference in blood glucose levels at the start and end of the treatment group with p <0.05. it was found that the control group's blood glucose reduction rate was -35.4 mg / dl. The highest reduction in blood glucose in the treatment group was in K7 respondents as much as 130 mg / dl and the highest increase in blood glucose was in K1 respondents as much as 159 mg / dl.Conclusion. There is an effect of giving dragon fruit to the decrease in blood glucose levels when patients with DM in the Tanjung Karang Health Center Work Area.